2022
DOI: 10.3390/su14116852
|View full text |Cite
|
Sign up to set email alerts
|

Green Bonds and Commodities: A New Asymmetric Sustainable Relationship

Abstract: In this study we examine the relationship between corporate green bonds and commodities (both perishable & non-perishable) that attracts very little attention in relative literature. For the first time, we investigate a long-term relationship between green bonds and commodities including a significantly higher number of commodities and observations. Furthermore, we adopt a novel methodology, the VaR (value at risk) based copulas, to describe the asymmetric risk spillover between green bonds and commodities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Lastly, by examining impulse responses at different points in time, the study revealed that stock prices tended to rise following a positive shock to clean energy, with this effect being particularly pronounced during economic recovery periods compared to other periods. In their study, Tsagkanos et al [49] delved into the correlation between corporate green bonds and a diverse array of commodities. Their work contributes to our comprehension of the enduring dynamics between green bonds and commodities.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Lastly, by examining impulse responses at different points in time, the study revealed that stock prices tended to rise following a positive shock to clean energy, with this effect being particularly pronounced during economic recovery periods compared to other periods. In their study, Tsagkanos et al [49] delved into the correlation between corporate green bonds and a diverse array of commodities. Their work contributes to our comprehension of the enduring dynamics between green bonds and commodities.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Since then, many studies investigated this segment and exerted the GB as “a risk-alleviating tool” for investors (Gatti & Florio, 2018; Jin et al, 2020; Mensi et al, 2022; Ortolano & Nissi, 2022; Uddin et al, 2022). Other strands of the literature demonstrated the portfolio diversification benefits for various investors (Gianfrate & Peri, 2019; Huynh et al, 2020; Karim & Naeem, 2022; Sohag et al, 2022; Tsagkanos et al, 2022). It has been well documented the stock market’s positive reaction to the GB announcements due to its signaling quality on issuers’ environmentally oriented activities (Bancel & Glavas, 2021; Laborda & Sánchez-Guerra, 2021; Roslen et al, 2017; Wang et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another is to adopt policies and strategies that anticipate future developments and environmental trends [30]. Recently, this has meant adopting the green commodities strategy [34], establishing a more friendly relationship with the climate, and reducing carbon emissions and other pollutants. This strategy, and other strategies responsive to outside factors, can help the business to create a good reputation, which enhances economic survival [5,6,34].…”
Section: Business Success and Sustainabilitymentioning
confidence: 99%